Evolution in small populations: evidence from the literature and experimental results - Tremblay, Raymond (Universidad de Costa Rica, 2015)
The great taxonomic diversity of the Orchidaceae is often attributed to adaptive radiation for specific polli- nators driven by selection for outcrossing. However, when one looks beyond the product to the process, the evidence for selection is less than overwhelming.